Digital Storytelling: Resistive Stories and the “Measurement” of Change - Thas Angela M. Kuga (Cultural Science)
In this paper, I interrogate our understanding of social change in the telling of self-representational digital stories, stories that speak from the perspective of the storyteller and which centre on the “I”. There is a growing audible criticism of the value of these digital stories if distribution and outreach of such stories do not reach both wider and critical audiences. As a digital storytelling practitioner, I examine these criticisms and draw attention first to our understanding of storytelling, and second to our understanding of audiences within an ancient oral tradition of humankind. There is no doubt that the digital in digital storytelling allows for a global arena of possibilities. However, it is these very same global possibilities within the digital that have possibly forced a cursory value on storytelling by the most important audience among audiences—the marginalised "I" who struggles for political, social and economic attention. The existential self is severely talked down to for not going beyond that one digital story or those few friends and family members. In these instances, that potential to transform “power over” into “power with” and “power within” the storytellers quickly disintegrates. What happens instead is an expansion of the pool of judges of narratives, a predominant and more overt phenomenon in the field of human rights. What form the final narrative takes in any digital storytelling project is often shaped by the interests of these “mediators” who turn “judges of narratives” when they mould and package these stories to be more palatable to their specific audiences and consumption needs. The storyteller's sense of existential peril is in this way prolonged. These untoward developments beg us to ask the question, “what change then are self-representational digital stories meant to bring about?”